Evaluation of eczema, asthma, allergic rhinitis and allergies among the grade-7 children of Iqaluit - Ahmed Ahmed; Allan Becker (Allergy, Asthma & Clinical Immunology, 2019)
Abstract Background Little is known about the prevalence of asthma, allergic rhinitis, eczema and allergies among Canadian Inuit children, especially those living in the arctic and subarctic areas. Methods A cross-sectional study among grade seven students attending schools in Iqaluit, the capital city of Nunavut, was conducted during the 2016/2017 school year. We used the International Study of Allergy and Asthma in Children (ISAAC) questionnaire with added questions relevant to the population. In addition, skin prick tests (SPT) were conducted to test for sensitization to common food and environmental allergens. Results The prevalence of current asthma is 5.2%, all of them were males and 2/3 of them were Inuit and all had a previous respiratory hospitalization. Past asthma prevalence is 8.6%, 60% males and 60% Inuit. There was an inverse relationship to crowdedness possibly as a confounding factor because of getting a higher prevalence among the non-Inuit who usually live in less crowded houses. Current allergic rhinitis prevalence is 8.6%, 60% of the cases were among the mixed Inuit/Caucasian ethnicity while no cases among the non-Inuit, there was a female predominance 3:2. Past history of allergic rhinitis prevalence is 10.3%, half of the cases were among the mixed ethnicity (5.2% of that ethnicity) followed by Inuit (3.4%) and non-Inuit (1.7%), female: Male ratio 1:1. Current eczema prevalence was 27.6%, with half of the cases among the mixed ethnicity (13.8% of that group), followed by Inuit (8.6%). There was a female predominance with protective effect of exclusive breastfeeding. Past eczema prevalence 34.5%, with half of the cases were among the mixed ethnicity (17.2% of that group), followed by Inuit (10.3%). There was a female predominance. We noted a high rate of sensitization to Cat at 29.2%, most of the cases were among the mixed ethnicity, while absent sensitization to other common inhalant allergens. Conclusion While being cautious about firm conclusions due to the small sample size and power, the ...